2017
DOI: 10.1089/neu.2016.4632
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment and Mood States after Spinal Cord Injury

Abstract: Spinal cord injury (SCI) is believed to be associated with high rates of cognitive impairment, which can result in complications in recovery. This study concerned two groups of adults with SCI. The first sample involved 150 participants with SCI who were assessed once for cognitive capacity with comparisons made with 45 able-bodied adults. Sample 2 were drawn from Sample 1, and included 88 participants with SCI who were prospectively assessed for mood states (anxiety, depressive mood, and fatigue) and pain int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
143
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(159 citation statements)
references
References 31 publications
7
143
1
5
Order By: Relevance
“…Cross-sectional studies had already detected a high frequency of cognitive impairment in patients with HAM/TSP (Gascón et al, 2017), suggesting that these alterations are an important clinical manifestation associated with myelopathy or even among asymptomatic carriers of HTLV (Craig et al, 2017). Patients presenting traumatic spinal cord injury showed 29% of impaired cognitive performance (Gascón et al, 2017), which may be related to multiple factors, such as inflammation, disability adjustment, depressive mood and medications.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies had already detected a high frequency of cognitive impairment in patients with HAM/TSP (Gascón et al, 2017), suggesting that these alterations are an important clinical manifestation associated with myelopathy or even among asymptomatic carriers of HTLV (Craig et al, 2017). Patients presenting traumatic spinal cord injury showed 29% of impaired cognitive performance (Gascón et al, 2017), which may be related to multiple factors, such as inflammation, disability adjustment, depressive mood and medications.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that the risk of an adult with SCI having cognitive impairment is nearly 13 times higher than that of someone without a SCI [18]. Moreover, the development of negative mood states was a significant problem in those patients with cognitive impairment after the first rehabilitation period [18].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies on the cognitive functions in people with SCI have been limited to the subacute stage (a few months after the injury). Cognitive dysfunction after SCI might be progressive due to several factors such as the cumulative effects of neuroactive drugs, brain inflammation, psychological factors, etc [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Although increased pressure and administrative burden related to the programme was reported by clinicians in this current study, the clinical benefit was recognised. Clinicians highlighted that dual expertise was required both in pain science and SCI in CBT-PMP delivery to address the highly complex nature of SCI NP management which can be compounded by other secondary health complications including spasticity, pressure ulcers and low mood [52][53][54]. An Australian survey reported that 81% of health care professionals providing care for SCI patients in the community feel inadequately resourced to manage SCI pain, due to a lack of training, knowledge and specialist access [55].…”
Section: Discussionmentioning
confidence: 99%